Plasto-elastohydrodynamic lubrication of heterogeneous materials in impact motion - Bai, Xueyu (2023)
The analysis of plastic evolution and material inhomogeneity is required for an accurate description of lubrication under impact loading. This work develops a semi-analytical model for heterogeneous materials in impact motion under plasto-elastohydrodynamic lubrication (PEHL) with limited inlet oil. A plasticity loop is proposed to obtain the accumulative plastic strain iteratively based on the analysis of the stress state. The inhomogeneous inclusion within the materials is homogenized with unknown eigenstrains according to the equivalent inclusion method. The surface displacements induced by the plastic strains and eigenstrains are introduced into the gap between the contact bodies to update the lubrication film thickness until the convergence is achieved. The consideration of plastic strains and eigenstrains makes the model more realistic for PEHL under impact loading. The responses including the pressure, film thickness, starvation parameter, residual deformation, temperature, and subsurface elastoplastic fields during the impact–rebound process are discussed. After the model validation against the reference data, the effects of material inhomogeneity and strain hardening on the lubrication response, as well as the typical features of elastic perfectly-plastic materials, are investigated to provide guidance for material reliability analysis.